Podcasts Created by University Students: A Way to Improve Subject Understanding, Connection with Peers, and Academic Performance - Hernandez-Lopez, Montserrat; Mendoza-Jimenez, Javier (Education sciences, 2025)
The integration of teacher-designed audiovisual tools in education has gained significant prominence, with podcasting emerging as a powerful pedagogical resource. While its benefits in enhancing learning flexibility and knowledge acquisition are well-documented, limited research examines the impact of student-generated podcasts. This study addresses that gap by investigating whether student-produced content enhances learning, improves academic performance, and enriches the classroom environment. A total of 190 students from the Tourism and Pedagogy degrees at the Universidad de La Laguna (Tenerife, Spain) participated by actively engaging in podcast creation as part of their coursework. They subsequently completed a survey assessing various aspects of the activity. Hypothesis testing revealed that student-generated podcasts not only improve academic outcomes but also cultivate a more dynamic and engaging learning experience. Findings suggest that beyond reinforcing subject mastery, podcasting yields intangible educational benefits, fostering deeper engagement and a more enriched classroom atmosphere. These results underscore the pedagogical value of student-driven content creation, positioning podcasting as an innovative instructional strategy that transcends conventional learning paradigms.